2018
DOI: 10.1002/solr.201800132
|View full text |Cite
|
Sign up to set email alerts
|

Band Dispersion and Hole Effective Mass of Methylammonium Lead Iodide Perovskite

Abstract: Solar cells incorporating organic–inorganic perovskites, especially methylammonium lead iodide (CH3NH3PbI3), have recently shown remarkable performances and therefore attracted wide interest. For understanding the origin of the high performance, the effective charge carrier masses of CH3NH3PbI3 are critical. However, reliable experimental data on its electronic band structure, which determines the effective mass, is yet to be provided. Here, the electronic structure of CH3NH3PbI3 single crystals is studied by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 31 publications
14
47
0
Order By: Relevance
“…Despite such difficulties, several research groups have challenged the ARUPS measurements on the single crystal halide perovskites. [196][197][198][199][200] We herein digest the cases of the single crystal methylammonium lead triiodide (CH 3 NH 3 PbI 3 ; MAPI). † † † Lee et al reported the ARUPS results on MAPI single crystal samples obtained under various excitation photon energies in a range of 74-200 eV.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite such difficulties, several research groups have challenged the ARUPS measurements on the single crystal halide perovskites. [196][197][198][199][200] We herein digest the cases of the single crystal methylammonium lead triiodide (CH 3 NH 3 PbI 3 ; MAPI). † † † Lee et al reported the ARUPS results on MAPI single crystal samples obtained under various excitation photon energies in a range of 74-200 eV.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Yang and coworkers succeeded in resolving the E-K 8 dispersion of the valence bands on MAPI single crystal samples by ARUPS under the excitation by He-Ia line (21.218 eV) and synchrotron radiation as well. 199 The crystal samples were cut along a specific crystal axis by using a knife blade in atmosphere and were immediately introduced into a ultra-high vacuum system. MCP-LEED observations confirmed that the surface lattice was predominantly the (001) face of the cubic MAPI at 350 K and 300 K, while slight incorporation of the tetragonal phase, which became intense on decreasing the temperature to 250 K, was also detected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For solar cell applications, only the tetragonal phase of MAPbI 3 at room temperature and the cubic high-temperature phase above 327 K are relevant. [32] With the mandatory requirements of non-centrosymmetry and piezoelectricity of the crystal structure being fulfilled, the question remains if any experimental evidence of ferroelectricity in MAPbI 3 in its tetragonal phase at room temperature exists. The MAPbI 3 unit cell comprises two perovskite cubes with slightly twisted PbI 6 octahedrons (purple).…”
Section: Experimental Evidence Of Ferroelectric Domains In Mapbi 3 Thmentioning
confidence: 99%
“…If aging experiments are carried out at elevated temperatures beyond the Curie temperature T C , the perovskite will furthermore undergo a (gradual) phase transition from the ferroelectric tetragonal phase to the paraelectric (non-ferroelectric) cubic phase [21], where the distinct ferroelectric domains vanish [22]. Common standards for accelerated aging, such as the IEC 61215, use temperatures of 65°C or 85°C, both of which are beyond the T C =55°C of MAPbI 3 [23].…”
mentioning
confidence: 99%